ADVOCATE HONORARIUM IN AN IJĀRAH BIL ‛AMĀL CONTRACT: Research Study at Law Firm Banda Aceh - Mufadhal (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2017)
In this modern era, advocates are needed as legal advisors or legal services for the public or clients dealing with existential problems. This research wants to know the mechanism for determining honorarium for advocates at law firms in Banda Aceh? The research method in this study uses a qualitative approach with the type of field research. The results showed that: First, the mechanism for determining the same honorarium for advocates in each advocate office that the author has researched such as an agreement in the form of cash at the beginning or a contract system, gradual payment, there is also a payment paid by a percentage system according to what agreement will be applied by both parties. Second, the advocate profession itself in fiqh muamalah is included in ijārah bil ‛amāl because it provides services in the form of legal services and service users provide payment in return and must be in accordance with the agreement of both parties whether written or not. based on the description above, it can be concluded that the mechanism for providing honoraria and the review of the ijārah bil ‛amāl contract on the mechanism for determining advocate honoraria in several advocate offices in Banda Aceh that the author has researched is in accordance with the value of wages in the ijārah bil ‛amāl contract.